Entrepreneurship attitudes and the Big Five: A cross-cultural comparison between Spain and the United States - Oliver, Amparo; Schneider, Barry H.; Galiana, Laura; Puricelli, David Alex; Schwendemann, Marc; Tomás, Jose Manuel (Anales de Psicología / Annals of Psychology, 2022)
Culture may interact with personality to facilitate or inhibit entrepreneurial behaviors. 296 undergraduates in the United States and 257 in Spain completed the Big Five Personality Inventory and the Entrepreneurial Attitudes Scale for Students (Mean age = 20.16 years; SD = 3.39). We hypothesized that across cultures, conscientiousness and openness would predict greater risk taking whereas neuroticism and agreeableness would be a negative correlate. Personality variables explained a larger proportion of the variance in entrepreneurial attitudes in the U.S. data. The associations between the personality dimensions and entrepreneurship varied considerably by country and gender. Significant positive correlations were found between conscientiousness and risk taking only for Spanish men. Neuroticism was significantly and negatively correlated with risk taking only for American participants.